Direct Observation of Amyloid β Behavior at Phospholipid Membrane Constructed on Gold Nanoparticles - Keishi Suga; Ying-Chen Lai; Miftah Faried; Hiroshi Umakoshi (International Journal of Analytical Chemistry)
Amyloid β (Aβ) is a potential biomarker of Alzheimer’s disease (AD), and its fibrillation behavior is of interest and value. In this study, the Aβ behaviors on phospholipid membranes were observed by Membrane Surface-Enhanced Raman Spectroscopy (MSERS) method. Phospholipid (PL) membranes, consisting of DMPC and DMPS with a molar ratio of 9:1, were fabricated on gold nanoparticles with diameter of 100 nm (Au@PL). Enhancement of the Raman intensity of Au@PL was increased by Aβ, with enhancement factor about 40. The H-bonding network was disturbed in presence of NaCl which covered Au@PL and made Au@PL away from one another. When Aβ was applied with Au@PL, the H-bonding network was disturbed just after mixing. As the reaction reaches to equilibrium, Aβ attracted neighbouring Au@PL and induced aggregation of Au@PL which blocked the aggregation prone site of Aβ to inhibit further fibrillation. Based on our method, the Aβ behaviors at lipid membrane surface can be directly observed via enhanced Raman signals.